Analisis Keselamatan Muatan di Kapal Kontainer MV A Daisen pada Voyage Nhava Sheva – Mundra (Indian Ocean) - Masnura At Thahirah; Anak Agung Ngurah Ade Dwi Putra Yuda; Dian Junita Arisusanty; Firdaus Sitepu (Pusat riset dan Inovasi Nasional, 2025)
Cargo safety on container ships is a crucial aspect of maritime operations, especially during voyages across open waters such as the Indian Ocean, which is characterized by extreme weather conditions and high waves. A common problem encountered is cargo damage or shifting due to non-compliance with proper stowage and securing procedures. This study aims to analyze the factors influencing cargo safety during container ship voyages in the Indian Ocean. The research employs a qualitative descriptive method using a case study approach. Data collection was conducted through historical document analysis related to cargo damage incidents and direct observation of the loading, stowage, and securing processes on board. The findings indicate that severe weather conditions, suboptimal cargo stowage techniques, and low compliance with safety procedures are the main factors contributing to cargo instability. Based on these findings, the study recommends enhanced training for crew members, the use of real-time cargo monitoring technologies, and stricter enforcement of regulations concerning container securing and stowage. These measures are expected to minimize the risk of incidents and improve overall cargo safety during maritime transport.